Wound complications after primary and repeated midline, transverse and modified Makuuchi incision: A single-center experience in 696 patients. Issue 20 (21st May 2021) - Hempel, Sebastian; Kalauch, Anne; Oehme, Florian; Wolk, Steffen; Welsch, Thilo; Weitz, Jürgen; Distler, Marius
Abstract : Abstract: There are 3 main types of incisions in major open, elective abdominal surgery: the midline incision (MI), the transverse incision (TI) and the modified Makuuchi incision (MMI). This study aimed to compare these approaches regarding wound complications and hernias, with a special focus on suture material and previous laparotomies. Patients who underwent elective abdominal surgery between 2015 and 2016 were retrospectively analyzed. Uni- and multivariate analyses were computed using stepwise binary and multifactorial regression models. In total, 696 patients (406 MI, 137 TI and 153 MMI) were included. No relevant differences were observed for patient characteristics (e.g., sex, age, body mass index [BMI], American Society of Anesthesiologists [ASA] score). Fewer wound complications (TI 22.6% vs MI 33.5% vs MMI 32.7%, P = .04) occurred in the TI group. However, regarding the endpoints surgical site infection (SSI), fascial dehiscence and incisional hernia, no risk factor after MI, TI, and MMI could be detected in statistical analysis. There was no difference regarding the occurrence of fascial dehiscence ( P = .58) or incisional hernia ( P = .97) between MI, TI, and MMI. In cases of relaparotomies, the incidence of fascial dehiscence ( P = .2) or incisional hernia ( P = .58) did not significantly differ between the MI, TI, or MMI as well as between primary and reincision of each type. On the other hand, the time to first appearance of a hernia after MMI is significantly shorter ( P = .03) than after MI or TI, even after previous laparotomy ( P = .003). In comparing the 3 most common types of abdominal incisions and ignoring the type of operative procedure performed, TI seems to be the least complicated approach. However, because the incidence of fascial dehiscence and incisional hernia is not relevantly increased, the stability of the abdominal wall is apparently not affected by relaparotomy, even by repeated MIs, TIs, and MMIs. Therefore, the type of laparotomy, especially a relaparotomy, can be chosen based on the surgeon's preference and planned procedure without worrying about increased wound complications.